OBSTRUÇÃO ESOFÁGICA EM LAMA GLAMA: RELATO DE CASO - Thomé, Tainara; Thomas, Lethycia Demczuk; Massa, Isadora Morais; Carneiro, Maico Fernando Wilges; Pinheiro, Fernanda (Anais de Medicina Veterinária, 2022)
.